2019
DOI: 10.1007/s00592-019-01311-y
|View full text |Cite
|
Sign up to set email alerts
|

Spousal diabetes status as a risk factor for incident type 2 diabetes: a prospective cohort study and meta-analysis

Abstract: AIMS:It is unclear if the presence of type-2 diabetes in one spouse is associated with the development of diabetes in the other spouse. We studied the concordance of diabetes among black and white participants in the Atherosclerosis Risk in Communities (ARIC) study and summarized existing studies in a meta-analysis. METHODS:We conducted a prospective cohort analysis of ARIC data from 8077 married men and women (mean age 54 years) without diabetes at baseline . Complementary log-log models that accounted for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 59 publications
4
18
1
Order By: Relevance
“…Furthermore, previous research has shown that there is spousal concordance concerning cardiovascular risk factors, such as smoking habits, sedentary life, overweight and high blood pressure [36], high alcohol consumption and a poor diet [37]. Recent meta-analyses have also confirmed high rates of spousal concordance for hypertension [38] and diabetes [39]. The spouses of stroke survivors observed in our sample had more comorbidities compared to the controls, which support these findings.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, previous research has shown that there is spousal concordance concerning cardiovascular risk factors, such as smoking habits, sedentary life, overweight and high blood pressure [36], high alcohol consumption and a poor diet [37]. Recent meta-analyses have also confirmed high rates of spousal concordance for hypertension [38] and diabetes [39]. The spouses of stroke survivors observed in our sample had more comorbidities compared to the controls, which support these findings.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, previous research has shown that there is spousal concordance concerning cardiovascular risk factors, such as smoking habits, sedentary life, overweight and high blood pressure (35), high alcohol consumption and a poor diet (36). Recent meta-analyses have also con rmed high rates of spousal concordance for hypertension (37) and diabetes (38). The spouses of stroke survivors observed in our sample had more comorbidities compared to the controls, which support these ndings.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, previous research has shown that there is spousal concordance concerning cardiovascular risk factors, such as smoking habits, sedentary life, overweight and high blood pressure (36), high alcohol consumption and a poor diet (37). Recent meta-analyses have also con rmed high rates of spousal concordance for hypertension (38) and diabetes (39). The spouses of stroke survivors observed in our sample had more comorbidities compared to the controls, which support these ndings.…”
Section: Discussionsupporting
confidence: 88%